2012
DOI: 10.1074/jbc.m112.398826
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the Structural Determinants of Fibroblast Growth Factor-Heparin Interactions

Abstract: Background: Heparan sulfate (HS) regulates the transport and signaling activities of fibroblast growth factors (FGF). Results: The molecular determinants of the interactions of FGFs and heparin were identified. Conclusion: There are clear molecular specificities determining the interactions of FGFs with the polysaccharide. Significance: The expansion of the FGFs in metazoan evolution parallels the diversification of the specificity of their interactions with heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
153
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(163 citation statements)
references
References 59 publications
10
153
0
Order By: Relevance
“…HS proteoglycans and heparin are well studied in this context (Pellegrini et al, 2000) as they promote cell proliferation and ERK1/2 activation (Guimond et al, 1993, Pye and Kumar, 1998, Delehedde et al, 2000. Recent studies have revealed distinct structural features of heparin that allow it to bind to Fgfs with a clear preference for the importance of 2-O sulfation of L-IdoUA (Xu et al, 2012;Jemth et al, 2002). The structural and functional aspects of HS and CS/DS in Fgf mitogenic activity are controversial, as both stimulation and inhibition have been reported (Guimond and Turnbull, 1999;Pye and Kumar, 1998;Fthenou et al, 2009;Yamada and Sugahara, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HS proteoglycans and heparin are well studied in this context (Pellegrini et al, 2000) as they promote cell proliferation and ERK1/2 activation (Guimond et al, 1993, Pye and Kumar, 1998, Delehedde et al, 2000. Recent studies have revealed distinct structural features of heparin that allow it to bind to Fgfs with a clear preference for the importance of 2-O sulfation of L-IdoUA (Xu et al, 2012;Jemth et al, 2002). The structural and functional aspects of HS and CS/DS in Fgf mitogenic activity are controversial, as both stimulation and inhibition have been reported (Guimond and Turnbull, 1999;Pye and Kumar, 1998;Fthenou et al, 2009;Yamada and Sugahara, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…41 The approach has been used to determine the HBS for FGF-1, -2, -3, -4, -6, -7, -9, -10, -17, -18 and -20. [41][42][43] The principal example shown in the text is for FGF-1, colloquially termed acidic FGF. The network analysis method described here identifies sequences within this protein that are highly similar to sequences found in other proteins known to bind heparin/HS, see Fig.…”
Section: Conserved Sequences In Proteinsmentioning
confidence: 99%
“…The 'Protect and Label' mass spectrometry performed on FGF-1 identified four heparin binding regions: KKPKLLY (amino acids (aa) 24-30); IKSTETGQYL (aa71-80); ISKKHAEKNWF (aa113-123); and VGLKKNGSCKRGPRTHYGQAILFLPL (aa124-150). 42 The analysis described above identified amino acid sequences within each of the previously identified regions in FGF-1 that interact with HS/heparin (Fig. 1).…”
Section: Conserved Sequences In Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of the FGF-7-FGFR2IIIb signaling axis contributes to the oncogenic process by activating intracellular kinase cascades including ERKdependent proliferation and AKT-mediated cell survival in breast cancer cells 37 , and antiFGFR2IIIb antibodies offer a new therapeutic option. 38 Since FGF-7 is one of the most structurally specific FGFs with respect to its requirement for a 3-O-sulfated motif to coordinate ligand-receptor complex assembly 39,40 , we investigated whether 3-OST3A expression may regulate its signaling pathway to trigger the tumor-suppressive effect observed in the lumA-MCF-7 cells. Supporting this assumption, our data show that reinstating 3-OST3A expression in these cells: i) impaired interactions between FGF-7 and HS chains, ii) inhibited proliferative signals via ERK dephosphorylation, and iii) boosted apoptotic signals via AKT dephosphorylation and p38 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%